FEDERAL STATE EDUCATIONAL STANDARDS IN LAW AS A GUARANTEE OF THE RIGHT TO HIGHER LEGAL EDUCATION - T. Yu. Leonova (Вестник Кемеровского государственного университета, 2015)
The paper analyzes the development and formation of the Federal State Educational Standards as guarantees of one of the constitutional rights of citizens to education, including higher education, since the adoption of the Constitution of theRussian Federationand up to the present day. The purpose of the study is to analyze the changes in the state approach in the field of standardization requirements and conditions to the content of legal education. The author makes conclusions about the meaning of the Federal State Standards of higher education in Law in modern conditions of the labour market. The author discovered that the timing of the adoption of these standards is violated, the lack of professional standards in the field of jurisprudence exists, which negatively affects the quality of education and its alienation from the employers’ needs. The author points at the shortcomings of the existing procedures for approval of Federal Educational Standards of higher education in Law with potential employers, the lack of a uniform methodology of employers’ participation in the process of formulation of standards and evaluation of results of the educational programmes development.